The old Santa Fe Trail - Vestal, Stanley, 1887-1957 (University of Nebraska Press, 1996)
The Santa Fe Trail was one of the two great overland highways originating in Missouri in the nineteenth century. Several decades before settlers streamed over the Oregon Trail, traders were heading southwest. The caravans carried the wares of Yankee commerce; they returned loaded with buffalo robes and beaver pelts and the rich metals of Mexican mines. The thousand-mile journey "was a perilous cruise across a boundless sea of grass, over forbidding mountains, among wild beasts and wilder men, ending in an exotic city offering quick riches, friendly foreign women, and a moral holiday," writes Stanley Vestal. Vestal begins where the trail does. He describes outfitting for the trip, the society formed for survival, the hunt for meat, landmarks, and the dangers. He evokes the history and legends surrounding the trail at every point, including figures like Kit Carson, Jedediah Smith, the Bent brothers, and Uncle Dick Wooton